Tekstilproduktion i dansk bronzealder - Felding, Louise; Matthes, Lilian; Tastesen, Vianna (Arkæologi i Slesvig-Archäologie in Schleswig, 2021)
So far, the archaeological research gives a good overview of the woolen textiles of the Early Bronze Age, especially the finds from the oak coffin burials. There are, however, still questions to ask about the production and manufacturing of wool, and how this can be seen in the material culture. Objects connected to textile production from settlement contexts in Denmark are still very sparse, loom weights and spindle whorls are not many to list. Of course, the conservation conditions and the missing knowledge of the material may explain the absence of such finds. However, a re-assessment of the objects from different Early Bronze Age settlements from Museum Sønderjylland actually shows that the textile production seems to have been more common than suggested until now – at least locally.